2007
DOI: 10.1261/rna.633808
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of two amino acids changes a promiscuous RNA binding protein into a sequence-specific RNA binding protein

Abstract: In yeast (Saccharoymces cerevisiae), the branchpoint binding protein (BBP) recognizes the conserved yeast branchpoint sequence (UACUAAC) with a high level of specificity and affinity, while the human branchpoint binding protein (SF1) binds the less-conserved consensus branchpoint sequence (CURAY) in human introns with a lower level of specificity and affinity. To determine which amino acids in BBP provide the additional specificity and affinity absent in SF1, a panel of chimeric SF1 proteins was tested in RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Comparison to SF1 highlights key differences in the secondary structure, position, and amino acid sequence of the QUA2 module that help rationalize the different stringencies of recognition of the U 1 A 2 C 3 nucleobases. These structural insights are in keeping with biochemical studies of chimeric Msl5-SF1 proteins that implicated the QUA2 module, and its Lys252-Arg253 dipeptide, as determinants of Msl5 target specificity and affinity in vitro (Garrey et al 2008). Yet, this dipeptide is clearly not decisive per se for Msl5 function in vivo, insofar as a yeast MSL5-(K252A-R253A) strain grows as well as wild-type MSL5 cells at 25°C-37°C .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Comparison to SF1 highlights key differences in the secondary structure, position, and amino acid sequence of the QUA2 module that help rationalize the different stringencies of recognition of the U 1 A 2 C 3 nucleobases. These structural insights are in keeping with biochemical studies of chimeric Msl5-SF1 proteins that implicated the QUA2 module, and its Lys252-Arg253 dipeptide, as determinants of Msl5 target specificity and affinity in vitro (Garrey et al 2008). Yet, this dipeptide is clearly not decisive per se for Msl5 function in vivo, insofar as a yeast MSL5-(K252A-R253A) strain grows as well as wild-type MSL5 cells at 25°C-37°C .…”
Section: Discussionsupporting
confidence: 70%
“…Lys252 also donates a hydrogen bond to the cytosine O2 carbonyl of the C 3 nucleobase. These features of the crystal structure neatly explain the results of Garrey et al (2008), who reported that the Lys252-Arg253 dipeptide of yeast Msl5 (which differs from the corresponding Arg240-Lys241 dipeptide in human SF1) is a key determinant of the distinctive high RNA affinity and sequence specificity of Msl5 versus SF1. The NMR structure of SF1 was not instructive on this front, insofar as the SF1 Arg240 residue is remote from the RNA (Liu et al 2001).…”
Section: Structural Basis For Branchpoint Rna Recognition By Msl5supporting
confidence: 57%
See 2 more Smart Citations
“…Also, two basic amino acids within the QUA2 domain (R240 and K241) that have been experimentally demonstrated to contribute to binding affinity and specificity without directly contacting RNA are not conserved in Sam68, but are in GLD-1, QKI, and HOW. 66 Together, the evidence suggests that the Sam68 QUA2 domain diverges significantly from the others, and as such its role in RNA recognition is not clear.…”
Section: Star Domain Structurementioning
confidence: 99%